miR-30b-5p Downregulation as a Predictive Biomarker of Coronary In-Stent Restenosis - Encarnación Gutierrez-Carretero; Isabel Mayoral-González; Francisco Jesús Morón; Mónica Fernández-Quero; Alejandro Domínguez-Rodríguez; Antonio Ordóñez; Tarik Smani (Biomedicines, 2021)
In-stent restenosis (ISR) is one of the main limitations of percutaneous coronary intervention (PCI) therapy with drug-eluting stents (DES) implantation. The aim of this study was to determine if circulating microRNAs (miRNAs) have diagnostic capability for determining ISR in a cohort of matched patients. Blood samples were collected from 55 patients who underwent previously PCI and were readmitted for a new coronary angiography. Patients were divided into subgroups comprising patients who presented ISR or not (non-ISR). A microarray analysis determined that up to 49 miRNAs were differentially expressed between ISR and non-ISR patients. Of these, 10 miRNAs are related to vascular smooth muscle and endothelial cells proliferation, migration, and differentiation, well-known hallmarks of vascular remodeling. Additionally, we identified that the expression of miR-30b-5p is significantly lower in serum samples of ISR patients, as compared to non-ISR. A further analysis demonstrated that miR-30b-5p provides better values of the receiver operator characteristic curve than other miRNAs and biochemical parameters. Finally, the in-silico analysis suggests that miR-30b-5p is predicted to target 62 genes involved in different signaling pathways involved in vascular remodeling. In conclusion, we determined for the first time that circulating mi-R30b-5p can reliably prognose restenosis in patient with implanted DES, which could be potentially helpful in the establishment of an early diagnosis and therapy of ISR.